Analisis Pengaruh Absensi Fingerprint Terhadap Disiplin, Motivasi, Dan Kinerja Pegawai Dinas Pekerjaan Umum Dan Penataan Ruang Aceh (Pupr Aceh) Menggunakan Metode Tam - Imilda; Alexandra, Rendy; Ahmad, Lukman (Jurnal Sistem Komputer (SISKOM), 2024)
This research aims to analyze the effect of using a fingerprint attendance system on employee discipline and motivation as well as its impact on the performance of employees of the Aceh Public Works and Spatial Planning Service (PUPR Aceh). The Technology Acceptance Model (TAM) method is used to understand the relationship between the effectiveness of implementing fingerprint attendance and discipline, motivation and performance variables. This research uses a quantitative approach by collecting data through questionnaires to 55 employees of the Aceh PUPR Service. Data were analyzed using the SPSS program for validity, reliability, descriptive, multiple linear regression and hypothesis testing. The research results show that the use of finger prints has a significant effect on employee discipline, but does not have a significant effect on motivation. Apart from that, there is a significant simultaneous influence between discipline and motivation on employee performance. The implication of this research is the importance of implementing fingerprint attendance technology in improving employee discipline, but special attention is needed in increasing motivation so that it can have a greater impact on employee performance.